THE INFLUENCE EDUCATIONAL LEVELS, TRAINING, COMPETENCIES AND LEADERSHIP QUALITIES ON EMPLOYEE WORK PRODUCTIVITY IN THE NATIONAL WORK UNIT REGION IV OF EAST NUSA TENGGARA PROVINCE - Se, Hyronimus; Langga, Lambertus (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2024)
This research aims to determine the influence of the level of education, training and competency on the work productivity of employees in the National Road Implementation Work Unit Region IV, East Nusa Tenggara Province. The sampling technique used is purposive cluster random sampling that is, each individual in each unit has a known opportunity to be clarified as a choice with a total of 39 respondents. Data collection methods through observation, questionnaires and documentation. The research results show that the variables level of education, training, competency and leadership quality partially have a significant effect on the work productivity of employees of the National Road Implementation Work Unit Region IV of East Nusa Tenggara Province by 85%.